Do wage expectations influence the decision to enroll in nursing college? - Juerg Schweri; Joop Hartog (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Given a severe nurse shortage in Switzerland, this paper investigates Swiss students choice for nursing college education and the impact of their ex ante wage expectations on college enrolment. The analysis contributes to a small developing literature that uses subjective wage expectation data to predict education choice. We surveyed a full cohort of healthcare trainees on upper-secondary level in their third year of training. The main result is that trainees who expected a lower starting wage when working as healthcare employee were more likely to enroll in a nursing college later on. This result suggests a role for policies that increase returns from studying nursing to attract students to nursing. In addition, the result confirms that subjective wage expectation data is useful in modeling individual choice.
Keywords: I21; I11; J24; 330